2020
DOI: 10.1126/science.aba9192
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent detection of the orbital angular momentum of light

Abstract: Applications that use the orbital angular momentum (OAM) of light show promise for increasing the bandwidth of optical communication networks. However, direct photocurrent detection of different OAM modes has not yet been demonstrated. Most studies of current responses to electromagnetic fields have focused on optical intensity–related effects, but phase information has been lost. In this study, we designed a photodetector based on tungsten ditelluride (WTe2) with carefully fabricated electrode geometries to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(104 citation statements)
references
References 27 publications
4
100
0
Order By: Relevance
“…The vectorial nature of light empowers full control of topological features with spatially phase-variant fields, revealing vortex beams carrying orbital angular momentum (OAM) and spin angular momentum (SAM) in addition to the well-known linear momentum 1 . Owing to the intriguing properties of optical vortices, OAM beams have found numerous applications in particle guiding and trapping, optical communication, quantum computation, holography and high-precision imaging, and novel light-matter interactions with topological materials [2][3][4][5][6][7][8] . Only quite recently have optical beams carrying a fractional orbital angular momentum (FOAM) 9,10 attracted considerable attention for their unusual properties and potential applications 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…The vectorial nature of light empowers full control of topological features with spatially phase-variant fields, revealing vortex beams carrying orbital angular momentum (OAM) and spin angular momentum (SAM) in addition to the well-known linear momentum 1 . Owing to the intriguing properties of optical vortices, OAM beams have found numerous applications in particle guiding and trapping, optical communication, quantum computation, holography and high-precision imaging, and novel light-matter interactions with topological materials [2][3][4][5][6][7][8] . Only quite recently have optical beams carrying a fractional orbital angular momentum (FOAM) 9,10 attracted considerable attention for their unusual properties and potential applications 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, two papers 10,11 have been published in Science side by side to address these challenges in OAMbased optical communication on chip. Zhang et al 10 reported an OAM-tunable vortex microlaser that provides chiral light states of variable topological charges at a single telecommunication wavelength.…”
mentioning
confidence: 99%
“…Zhang et al 10 reported an OAM-tunable vortex microlaser that provides chiral light states of variable topological charges at a single telecommunication wavelength. Ji et al 11 demonstrated an OAM photodetector based on tungsten ditelluride (WTe 2 ) to facilitate direct characterization of the topological charge of a vortex beam. These two works provide routes for the development of fourth-generation (4.0) vortex technology on chip.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Angle resolved photoemission spectroscopy (ARPES), however, revealed that bi-layers could also be weakly semimetallic with a small negative gap [12]. A combination of inverted bands, strong spin-orbit coupling and low crystal symmetry makes few-layer WTe2 an ideal system for studying topological effects such as the nonlinear anomalous Hall effect [13] [14] [15] and various unusual photogalvanic effects [16] [17] [18]. The goal of the present study is to explore the evolution of the low-energy electrodynamics of WTe2 from monolayer to few-layer variants (Fig.…”
mentioning
confidence: 99%